Proteomic and metabolomic analyses uncover integrative mechanisms in Sesuvium portulacastrum tolerance to salt stress - Cao, Dingding; Zhang, Wenbin; Yang, Nan; Li, Ziling; Zhang, Chaoyue; Wang, Dan; Ye, Guiping; Chen, Jianjun; Wei, Xiangying (Frontiers in Plant Science, 2023)
Salt stress is a major constraint affecting crop productivity worldwide. Investigation of halophytes could provide valuable information for improving economically important crops to tolerate salt stress and also for more effectively using halophytes to remediate saline environments. Sesuvium portulacastrum L. is a halophyte species widely distributed in tropical and subtropical coastal regions and is able enables to absorb a quite large amount of sodium (Na). In this study, we evaluate S. portulacastrum responses to different concentrations of NaCl and specifically compared physiological, proteomic, and metabolomic changes inof S. portulacastrum after being exposed to 0.4 M NaCl for 24 h as immediate salt stressresponses (IS) to 14 days as adaptative salt stressresponses (AS). A total of 47 and 248 differentially expressed proteins (DEPs) were enriched in leaves and 248 DEPs in roots, respectively. KEGG analysis showed that DEPs, especially those occurring infrom roots, were largelymainly related toenriched in metabolic pathways. Root metabonomics analysis showed that enriched 292 IS differentially expressed metabolites (DEMs)-DEMs occurred in IS plants and 371 in AS plants. Among them-DEMs, , 20.63% ofand the highest proportion of up-regulated DEMs were related to phenolic acid metabolisms (20.63%). Based on the integrative analysis of proteomics and metabolomics, sSignal transduction and phenolic acids synthesis and metabolism related DEPs and DEMs appeared to bewere crucial for S. portulacastrumin plant salt to toleratence salt stress. A working model for integrative responses was proposed. Specifically, Through the integration analysis of proteomics and metabolomics, we put forward that Ca 2+ , ABA, and JA signalings worked together to regulate plant growth and development underin salt stress adaption. TheSalt stress initiallyfirstly activatedpromoted the phenylpropanoid biosynthesis pathway through Ca 2+ calcium ion signal transduction and increased the content of metabolites, such as coniferin. M; meanwhile, the stressit inhibited MAPK signaling pathway through ABA and JA signal 样式定义: 样式1: 字体: (默认) Times New Roman